2019
DOI: 10.1007/s10980-019-00867-y
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-level naturalness of conservation easements in a mixed-use matrix

Abstract: Context With underrepresentation of habitats in publicly protected areas, attention has focused on the function of alternative land conservation mechanisms. Private conservation easements (CEs) have proliferated in the United States, yet assessing landscape-level function is confounded by varying extent, resolution, and temporal scale. Objectives We developed and tested an assessment tool to evaluate interacting spatial, social, and environmental attributes of easements relative to the degree of human modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
4
1
Order By: Relevance
“…Our finding that easements tended to occur in locations of higher biodiversity contrasts with results for counties on the west coast of the United States (Williamson et al 2018) and parcels in Appalachia (Fouch et al 2019). These differences may be a function of the different resolutions of the analyses (i.e., the Modifiable Areal Unit Problem [Jelinski & Wu 1996]) or may reflect the importance of accounting for variation in the probability that a location is available for an easement prior to comparing easement locations with and without easements.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that easements tended to occur in locations of higher biodiversity contrasts with results for counties on the west coast of the United States (Williamson et al 2018) and parcels in Appalachia (Fouch et al 2019). These differences may be a function of the different resolutions of the analyses (i.e., the Modifiable Areal Unit Problem [Jelinski & Wu 1996]) or may reflect the importance of accounting for variation in the probability that a location is available for an easement prior to comparing easement locations with and without easements.…”
Section: Discussioncontrasting
confidence: 99%
“…The majority of classifications of landscape naturalness found in the literature are related to the degree of anthropogenic transformation of the landscape (anthropogenization), and distinguish among devastated, cultural, natural, and primeval landscapes [22]. Therefore, naturalness is one of the factors that influence the value of the landscape [23] and determines the optimal natural landscape protection strategy [24][25][26]. Researchers differ in the criteria [27][28][29][30] that they use to measure naturalness (dividing it into the categories: Urban landscape, city park, commercial forest, or natural forest [31] based on certain levels of transformation [32], the share of natural, semi-natural, and synanthropic plant communities [33], an indicator of the wildness of the landscape [34], the time of human interference [31], or the cultural features that coexist in the landscape [35]).…”
Section: Naturalness Of the Landscapementioning
confidence: 99%
“…Despite the considerable investment in conservation easements, their effectiveness in achieving biodiversity conservation objectives is often not high. Fouch et al (2019) found that privately conserved lands did not differ significantly from non‐conserved lands in the degree of human modification in North Carolina. In a region of Idaho, private land in conservation easements provided increased representation within the protected areas network for only 10% of the ecosystem types and protected potential landscape connectivity only slightly more effectively than randomly allocated areas (Graves et al, 2019).…”
Section: Discussionmentioning
confidence: 99%